Sustained wakefulness and visual attention: moderation by chronotype - Barclay, N; Myachykov, A (Springer, 2016)
Introduction Attentional networks are sensitive to sleep deprivation and increased time awake. However, existing evidence is inconsistent and may be accounted for by differences in chronotype or time-of-day. We examined the effects of sustained wakefulness over a normal “socially constrained” day (following 18 hours of sustained wakefulness), following a night of normal sleep, on visual attention as a function of chronotype. Method 26 good sleepers (mean age: 25.58; SD=4.26; 54% male) completed The Attention Network Test (ANT) at two time-points (baseline at 8am; following 18 hours sustained wakefulness at 2am). The ANT provided mean reaction times (RT), error rates, and the efficiency of three attentional networks – alerting, orienting and executive control/conflict. The Morningness-Eveningness Questionnaire measured chronotype. Results Mean RTs were longer at time 2 compared to time 1 for those with increasing eveningness; the opposite was true for morningness. However, those with increasing morningness exhibited longer RT, and made more errors, on incongruent trials at time 2 relative to those with increasing eveningness. There were no significant main effects of time or chronotype (or interactions) on attentional network scores. Conclusion Sustained wakefulness produced differential effects on visual attention as a function of chronotype. Whilst overall our results point to an asynchrony effect, this effect was moderated by flanker type. Participants with increasing eveningness outperformed those with increasing morningness on incongruent trials at time 2. The preservation of executive control in evening-types following sustained wakefulness is likely driven by differences in circadian phase between chronotypes across the day.